The potential of stem cell therapy to tackle visual impairment - Murtuza Hassan; Sheerien Kareem Rajput; Jahan Salma; Karim F. Damji (Journal of the Pakistan Medical Association, 2023)
Visual impairment adversely impacts quality of life and affects more than 295 million individuals globally. Currently, there is no cure or tissue regenerative approaches in clinical practice for vision loss caused by corneal disease, glaucoma, cataracts, macular degeneration, diabetic retinopathy, and inherited retinal disease. Stem cells-based therapeutic approaches to diseases causing moderate to severe visual impairment have shown encouraging outcomes in animal models and in vitro studies. The goal of this narrative review is to describe and evaluate the potential of stem cell-based treatment, and their advantages and safety concerns in treating conditions causing vision loss. Key words: Vision, Retinal, Macular, Cataract, Glaucoma, Corneal, Stem Cells, hereditary, pluripotential